Narrative Theory and Cognition - Walsh, Richard (Revista Letras, 2026)
Text resulting from the lecture presented at the XIV EBICC, held at the Federal University of Paraná in September 2024. It analyzes narrative as a mode of meaning production that substantiates human thought. Four directions are explored: the cognitive sense of the stories we tell each other, the cognitive benefits of elementary narrative forms, the inherent limits of narrative meaning production, the conditions of continuity between the most elementary narrative cognition and narrative culture in general.